Impact of WTO’s Trade Liberalisation on Selected Food Crops in Pakistan (The Pakistan Development Review, 2008)
There is a great potential in Pakistan for production of all types of food commodities due to vast natural resource base, covering various ecological and climatic zones. Most of the agricultural commodities produced in the country are consumed by the local population while the rest is exported in the form of primary products and some value added products. Previously, Pakistani products had a good market overseas with no restrictions of quality and quantity but under the changing environment affected by WTO, it is expected that Pakistan will face a strong competition in the agriculture sector from its competitors in the world market. According to the neoclassical trade theory, trade flows and pattern will develop along the lines of comparative advantage and competitiveness that can act as indicators of trade potential and direction. There has been extensive government involvement in the determination of the overall structure of agriculture and its patterns of production, employment and trade. Pakistani government has been intervening in agriculture sector in the past in order to support agricultural production, income supports, ensure food security, improve the balance of trade, reduce consumer prices, address environmental and regional concerns and to pursue sanitary and phyto-sanitary objectives [Hassan (1995)]. Pakistan is a founding member of the General Agreement on Tariffs and Trade (GATT) since its creation. Following the Uruguay Round negotiations, all agricultural products were brought under multinational trade rules by WTO, under the Agreement on Agriculture. This established a framework to begin liberalising agricultural trade through the reduction of import duties (tariffs), trade-distorting production subsidies and export subsidies. Prior to the Uruguay Round, trade in agriculture was highly distorted. Market access for agricultural products was limited as most markets were restricted by physical import barriers. The presence of massive domestic subsidies led to overproduction of temperate crops in the developed countries that led to excess supply, and export subsidies were used to dump the surplus agricultural output in international markets. This resulted in depressed market prices and, in spite of being low-cost producers of agricultural products; developing countries could not compete with the subsidised exports from developed countries.